PROBLEMS OF SALES FORCE: A STUDY WITH REFERENCE TO REAL ESTATE SECTOR - Karumuri, Venkateswarlu (International Journal of Research -GRANTHAALAYAH, 2019)
Real estate sector is one of the pre dominantly growing sectors in India as it is seen as both need fulfilment and as well as investment opportunity that gives stable returns over a period of time. Earlier the Indian real estate sector is in the hands of informal real estate agents and brokers. Now a days real estate sectors is growing in a more formal manner due to the government policies, rules and regulations. The government’s allowance of FDI into real estate and announcement of regional balanced development increased the employment opportunities further. As this sector is highly influenced by so many players the real estate firms started focusing on increasing the goodwill to reach the customers. One of the goodwill ambassadors for the companies, are the sales force as they will be in continuous contact with the customer throughout the process. Sales force face many professional problems during the delivery of their work. A study has been conducted to understand the problems faced by real estate sales force in their jobs in the select cities of Andhra Pradesh. Anova study, mean and standard deviation techniques were used to project the results. The study identified significant problems faced by real estate sales force and offered suggestions to real estate firms in Andhra Pradesh.